2014
DOI: 10.3389/fpsyg.2014.00205
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive enhancement after training in preschoolers from diverse socioeconomic backgrounds

Abstract: The association between socioeconomic status and child cognitive development, and the positive impact of interventions aimed at optimizing cognitive performance, are well-documented. However, few studies have examined how specific socio-environmental factors may moderate the impact of cognitive interventions among poor children. In the present study, we examined how such factors predicted cognitive trajectories during the preschool years, in two samples of children from Argentina, who participated in two cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 93 publications
3
44
0
8
Order By: Relevance
“…Although the EF tests presented here had been used in previous studies and proved to be useful in detecting changes produced by other types of interventions [76], it is possible that they failed to detect the effects of this broader intervention whereas grades performed better. However, whether the battery used had enough sensitivity remains an open question and cannot be answered with the applied design.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although the EF tests presented here had been used in previous studies and proved to be useful in detecting changes produced by other types of interventions [76], it is possible that they failed to detect the effects of this broader intervention whereas grades performed better. However, whether the battery used had enough sensitivity remains an open question and cannot be answered with the applied design.…”
Section: Discussionmentioning
confidence: 67%
“…During recent years, several studies have shown that EF can be improved following a systematically-increasing EF-demand schedule [70][71][72][73][74][75][76][77][78][79]. However, few of those trainings have been conducted by teachers in classes.…”
Section: Interventions Aimed At Optimising Cognitive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, other factors, such as gender, have been found to influence the outcome of training in some studies (Söderqvist, Bergman Nutley, Ottersen, Grill, & Klingberg, 2012) but not others (Klingberg et al, 2005). It remains possible that a number of other factors that have been largely unexplored (e.g., socioeconomic status, although see Segretin et al, 2014) may play a role, at least in some interventions.…”
Section: Baseline Performance and Other Individual Difference Factorsmentioning
confidence: 99%
“…In addition, specific mediators of the effects of childhood poverty have been identified, including low parental education levels, little cognitive stimulation at home, limited language interactions from parents to children, overcrowding, poor housing conditions, pre and post-natal stress and anxiety or depression on the part of parents (Noble & Farah, 2013;Segretin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%